(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents an overview of modern innovative materials used in the construction industry, with an emphasis on their properties that contribute to sustainable development, as well as their strength and energy efficiency characteristics. A classification of the materials under consideration is proposed, including geopolymer concretes, nanostructured composites, phase-change materials, aerogels and biomaterials. Particular attention is paid to the role of these materials in the formation of a sustainable architectural environment capable of adapting to modern environmental and energy challenges. An analysis of strength and thermal insulation indicators is carried out, comparative characteristics of various materials are presented and prospects for the use of innovative solutions in energy-efficient construction are revealed. This study is based on current scientific publications, international standards and experience in implementing sustainable design projects.